Herbicolin A, an antifungal lipopeptide produced by Pantoea agglomerans APC 4211 is a promising biocontrol agent against food spoilage fungi - Eleni Kamilari; Paula M. O'Connor; Jerry Reen; Promi Das; Aiswariya Deliephan; Daragh Hill; Oxana Fursenko; Jonathan Weise; Ay Sha Naomi Moore; Colin Hill; Catherine Stanton; Paul R. Ross (International Journal of Food Microbiology, 2026)

Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

The Integration of Fire Ecology and Freshwater Ecosystems in North America: Knowledge Gaps and Research Needs - Morgan L. Piczak; Ava J. A. Sergio; Caliyena R. Brown; Waverley S. Birch; Rebecca L. Flitcroft; Meg A. Krawchuk; Colin P. R. McCarter; Jonathan W. Moore; Brendan P. Murphy; Brooke E. Penaluna; Prabha A. Rupasinghe; Victoria Steblaj; et al. (Global Change Biology, 2026)
Wildfires, unplanned fires that start and spread under the influence of weather and fuel composition, are increasing in frequency, duration, and severity across North America. While wildfires are one component of wildland fire, a broader natural process in many ecosystems, their changing behavior poses growing ecological and management challenges. Although wildfire is widely recognized as an important disturbance, empirical research quantifying its impacts on freshwater ecosystems remains limited and fragmented. As a result, our understanding of how wildfire affects imperiled freshwater systems remains underdeveloped. The objective of this review was to synthesize the existing empirical literature and identify key knowledge gaps to guide future research on wildfire–freshwater interactions across both biotic and abiotic components. At the biological scale, uncertainties remain around species‐ and community‐level responses (e.g., direct and indirect effects on biota). Freshwater habitat dimensions should also be the focus of further research, including alterations to physical structure (e.g., vegetation) and physicochemical conditions (e.g., temperature). From a management perspective, critical questions relate to fire‐informed restoration (e.g., specialized techniques, role of managed burns) and strategies for enhancing ecosystem resilience (e.g., identifying relevant indicators, links to watershed health). Understanding how land‐use change (e.g., forestry) and climate change interact to influence wildfire regimes and generate cumulative effects across landscapes is also essential in this new wildfire reality. To advance research and practice, we recommend comprehensive monitoring, standardization of methods and indicators, recognition of the role of cultural and prescribed burns, meaningful knowledge co‐production, and bridging the gap between scientific knowledge and management action.

Identification of Dolly Varden (Salvelinus malma) in the Canadian Arctic east of the Mackenzie River - Spencer Y. Weinstein; Amanda Dumond; Tracey N. Loewen; James D. Reist; Matthew C. Hale; Colin P. Gallagher; Jean-Sébastien Moore; Les N. Harris; Ross F. Tallman; Robert Bajno; Zoya A. Martin; Paul M. Craig; et al. (Environmental Biology of Fishes, 2026)

Photosensitiser-incorporated microparticles for photodynamic inactivation of bacteria - Jessica V. Moore; Matthew P. Wylie; Gavin P. Andrews; Colin P. McCoy (Journal of Photochemistry and Photobiology B: Biology, 2023)

Are we there yet? Management baselines and biodiversity indicators for the protection and restoration of subtidal bivalve shellfish habitats - Jose M. Fariñas-Franco; Robert L. Cook; Fiona R. Gell; Dan B. Harries; Natalie Hirst; Flora Kent; Rebecca MacPherson; Colin Moore; James M. Mair; Joanne S. Porter; William G. Sanderson (Science of The Total Environment, 2023)

Comparative biology of the grenadiers Macrourus caml and M. whitsoni in the Ross Sea region, Antarctica - Bradley R. Moore; Steven J. Parker; Peter M. Marriott; Colin Sutton; Matthew H. Pinkerton (Frontiers in Marine Science, 2022)
The grenadiers Macrourus caml and M. whitsoni form a significant bycatch component of longline fisheries for Antarctic toothfish ( Dissostichus mawsoni ) in the Southern Ocean. A lack of species-level biological and catch data has to date hindered the development of quantitative assessments for these deepwater species. This paper examines species- and sex-specific life histories of M . caml and M . whitsoni in the Ross Sea region, Antarctica, from samples collected from the commercial fishery and research collections. Macrourus caml was found to live longer, grow slower, and attain a larger maximum length than M . whitsoni , reaching at least 65 years of age and 97 cm total length (TL) vs. 43 years and 78 cm TL for M . whitsoni . In addition, M . caml attains a larger length for a given age and a greater weight for a given length. For each species, females of a given age were larger and reached a greater maximum age than males. Assuming that selectivity of the fishing gear is related to fish size, greater fishing pressure on females than males is likely, and was evidenced by female-biased sex ratios of both species. Estimates of natural and fishing mortality rates were low for both species. Despite having a shorter lifespan and attaining a smaller maximum length, M . whitsoni matured later in life and at larger lengths than M . caml . Although sampling opportunities are constrained seasonally due to sea ice cover, gonad staging and interannual patterns in gonadosomatic indices suggest prolonged spawning for both species, with available data indicating peak spawning during austral summer. The differences in life history observed between these two closely related and morphologically similar species illustrates the importance of understanding species-specific life histories to infer responses to exploitation, provide key biological inputs to inform parameters for future risk assessments and ecosystem models as well as baseline information for comparative work over both time and space, contribute to greater clarity in managing fisheries that interact with these two species, and further our understanding of grenadier life history.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A comparison of trends in population size and life history features of Atlantic salmon (Salmo salar) and anadromous and non-anadromous Brown trout (Salmo trutta) in a single catchment over 116 years - Colin E. Adams; Hannele M. Honkanen; Ellen Bryson; Isabel E. Moore; Malcolm MacCormick; Jennifer A. Dodd (Hydrobiologia, 2022)
We use a long time series of catch abundance from a recreational fishery over 116 years to look for population trends in Atlantic salmon, and anadromous (sea trout) and non-anadromous (brown) trout for a single catchment, Loch Lomond, west central Scotland. Year strongly predicted variation in catches but catch effort did not meaningfully increase explained variation. Salmon showed periods of increasing and decreasing trends, for sea trout and brown trout there was an overall declining trend. Since 1952, Lomond salmon population trends differed from both wider Scotland and southern Europe, indicating that the Lomond population is partially buffered from drivers of change in salmon populations more widely. In contrast Lomond sea trout showed a similar declining trend to that of populations from the wider west of Scotland over this period. The Lomond populations showed some evidence of shorter-term cycling patterns; the drivers for which are unknown. Body size in salmon and sea trout declined but increased in brown trout; salmon returned to freshwater later, and the relative proportion of all caught trout that were anadromous increased across the time series. This study shows a long and protracted period of fundamental change to populations of these two species over 116 years.

Marine and freshwater regime changes impact a community of migratory Pacific salmonids in decline - Kyle L. Wilson; Colin J. Bailey; Trevor D. Davies; Jonathan W. Moore (Global Change Biology, 2022)
Marine and freshwater ecosystems are increasingly at risk of large and cascading changes from multiple human activities (termed “regime shifts”), which can impact population productivity, resilience, and ecosystem structure. Pacific salmon exhibit persistent and large fluctuations in their population dynamics driven by combinations of intrinsic (e.g., density dependence) and extrinsic factors (e.g., ecosystem changes, species interactions). In recent years, many Pacific salmon have declined due to regime shifts but clear understanding of the processes driving these changes remains elusive. Here, we unpacked the role of density dependence, ecosystem trends, and stochasticity on productivity regimes for a community of five anadromous Pacific salmonids (Steelhead, Coho Salmon, Pink Salmon, Dolly Varden, and Coastal Cutthroat Trout) across a rich 40‐year time‐series. We used a Bayesian multivariate state‐space model to examine whether productivity shifts had similarly occurred across the community and explored marine or freshwater changes associated with those shifts. Overall, we identified three productivity regimes: an early regime (1976–1990), a compensatory regime (1991–2009), and a declining regime (since 2010) where large declines were observed for Steelhead, Dolly Varden, and Cutthroat Trout, intermediate declines in Coho and no change in Pink Salmon. These regime changes were associated with multiple cumulative effects across the salmon life cycle. For example, increased seal densities and ocean competition were associated with lower adult marine survival in Steelhead. Watershed logging also intensified over the past 40 years and was associated with (all else equal) ≥97% declines in freshwater productivity for Steelhead, Cutthroat, and Coho. For Steelhead, marine and freshwater dynamics played approximately equal roles in explaining trends in total productivity. Collectively, these changing environments limited juvenile production and lowered future adult returns. These results reveal how changes in freshwater and marine environments can jointly shape population dynamics among ecological communities, like Pacific salmon, with cascading consequences to their resilience.

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

Publishing and sharing multi-dimensional image data with OMERO - Jean-Marie Burel; Sébastien Besson; Colin Blackburn; Mark Carroll; Richard K. Ferguson; Helen Flynn; Kenneth Gillen; Roger Leigh; Simon Li; Dominik Lindner; Melissa Linkert; William J. Moore; et al. (Mammalian Genome, 2015)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Successful cognitive aging in persons living with HIV infection - Lauren Malaspina; Steven Paul Woods; David J. Moore; Colin Depp; Scott L. Letendre; Dilip Jeste; Igor Grant (Journal of NeuroVirology, 2011)

Palatability mapping: a koala's eye view of spatial variation in habitat quality - Ben D. Moore; Ivan R. Lawler; Ian R. Wallis; Colin M. Beale; William J. Foley (Ecology, 2010)
Ecologists trying to understand the value of habitat to animals must first describe the value of resources contained in the habitat to animals and, second, they must describe spatial variation in resource quality at a resolution relevant to individual animal foraging. We addressed these issues in a study of koalas ( Phascolarctos cinereus ) in a Eucalyptus woodland. We measured beneficial and deterrent chemical characteristics as well as the palatability of trees using a near‐infrared spectroscopic model based on direct feeding experiments. Tree use by koalas was influenced by tree size and foliar quality but was also context‐dependent: trees were more likely to be visited if they were surrounded by small, unpalatable trees or by large, palatable trees. Spatial autocorrelation analysis and several mapping approaches demonstrated that foliar quality is spatially structured in the woodland at a scale relevant to foraging decisions by koalas and that the spatial structure is an important component of habitat quality.

Determination of total antibiotic resistance in waterborne bacteria in rivers and streams in Northern Ireland: Can antibiotic-resistant bacteria be an indicator of ecological change? - John E. Moore; Juluri R. Rao; Peter J. A. Moore; B. Cherie Millar; Colin E. Goldsmith; Anne Loughrey; Paul J. Rooney (Aquatic Ecology, 2010)

Employment of 16S rDNA gene sequencing techniques for improved identification of difficult-to-identify bacterial veterinary pathogens - John E. Moore; Yasunori Maeda; Jiru Xu; B. Cherie Millar; Peter H. Herold; V. M. J. Browne-Lauwers; Colin E. Goldsmith; Anne Loughrey; Paul J. Rooney; J. Stuart Elborn; Motoo Matsuda (World Journal of Microbiology and Biotechnology, 2008)

Locus heterogeneity in autosomal recessive congenital cataracts: linkage to 9q and germline HSF4 mutations - Tim Forshew; Colin A. Johnson; Shagufta Khaliq; Shanaz Pasha; Catherine Willis; Rashida Abbasi; Louise Tee; Ursula Smith; Richard C. Trembath; Syed Qasim Mehdi; Anthony T. Moore; Eamonn R. Maher (Human Genetics, 2005)

Imprinted methylation profiles for proximal mouse Chromosomes 11 and 7 as revealed by methylation-sensitive representational difference analysis - Jo Peters; Gavin Kelsey; Gudrun E. Moore; Rachel Smith; Philippe Arnaud; Michael A. Preece; David Monk; Philip Stanier; Colin V. Beechey (Mammalian Genome, 2003)

DDC and COBL, flanking the imprinted GRB10 gene on 7p12, are biallelically expressed - Megan P. Hitchins; Louise Bentley; David Monk; Colin Beechey; Jo Peters; Gavin Kelsey; Fumitoshi Ishino; Michael A. Preece; Philip Stanier; Gudrun E. Moore (Mammalian Genome, 2002)

Spawning site selection by two galaxiid fishes, Galaxias anomalus and G. depressiceps , in tributaries of the Taieri River, South Island, New Zealand - Suzanne J. Moore; Richard M. Allibone; Colin R. Townsend (New Zealand Journal of Marine and Freshwater Research, 1999)
Recent studies have led to the recognition of Galaxias depressiceps and reinstatement of Galaxias anomalus . The two species maintain near allopatric distributions and it has been suggested that spawning habitat availability, at least partially, controls the distribution of these species. The spawning habitat of each species was determined and an assessment of the influence of spawning habitat availability on the distribution of the two species was carried out. Factors that may have influenced the onset of spawning were also examined. We found that G. depressiceps selected spawning sites with a high proportion of boulder substrata and nests were found on the underside of or between boulders. G. anomalus spawned within the streambed substrata, under boulders or cobbles, in shallow water and narrow channels relative to the available habitat. Suitable boulder spawning substratum for G. depressiceps in the G. anomalus sites was limited and this supports the hypothesis that spawning habitat availability influences G. depressiceps distribution. Conversely G. anomalus spawning habitat was available in G. depressiceps streams, indicating that spawning habitat limitations are not restricting G. anomalus . The onset of spawning, for both species, did not appear to be related to daylight, phase of the moon, or stream water level, but all species started spawning as water temperatures rose. The proximity of G. anomalus spawning sites to the stream edge and their occurrence in poorly consolidated substrata presents two management issues. Water abstraction may expose spawning sites if stream water levels are lowered, and these sites are vulnerable to trampling by stock.

Rearing dover sole larvae onTisbe andArtemia diets - Philip L. Heath; Colin G. Moore (Aquaculture International, 1997)